Translation Teaching Model in Offline, Online, and Hybrid Mode - Arif Hidayat; Fachri Helmanto (Prodi. Pendidikan Bahasa Inggris, FKIP, Universitas Kristen Indonesia, 2023)
Reviewing translation teaching from the nature of the basic skills that must be possessed, students have at least mastered two languages based on their respective linguistic rules. This study aims to analyze the translation teaching model in offline, online, and hybrid mode. This research uses a case study method with a qualitative approach. The subject of this research is learning English Indonesian Translation classes from 2019 to 2022 at UBSI. Research data analysis techniques use interactive data techniques and are validated by conducting data source triangulation techniques. This study reveals that translation teaching requires student readiness by requiring students to master a number of courses or at least have attended and passed the required lectures. Offline, online, and hybrid translation teaching at UBSI is carried out consistently and continuously. UBSI uses a collaborative translation teaching model by combining two translation teaching models through technology. The limitations of this research are limited to the level of researcher participation in several quality assurance processes. However, this research succeeded in uncovering the potential of technology as part of a collaborative translation teaching model.